New wave clay : ceramic design, art and architecture - Morris, Tom, ....- (Amsterdam : Frame Publishers, 2018)
This book is a survey of eighty international ceramicists who bridge the worlds of product design, interiors, fine art, and luxury craftsmanship.
Keywords: Keramiek